Ecological Factors in Settlement Marketing Projection for Balmazujvaros - Tarné Klutsik, Andrea (Acta Agraria Debreceniensis, 2003)
Marketing is a crucial tool for regional and local governments, and should be better employed before Hungary joins the European Union.In my article I refer to the five-step process of environmental and situational analyses indispensable for a strategic plan, which serves as the basis for a marketing concept for a settlement. Furthermore, I present the necessity of the macro, mezo and local levels of environmental analyses. This part of my article is aimed at clarifying the notion of ecological marketing. My objective is to discuss its relation to settlement marketing.The second part of my article investigated the emergence of ecological factors in settlement marketing, in its process, using the example of Balmazújváros. I presented the correlation between Balmazújváros and Hortobágy National Park, from which I investigated primarily important areas focusing on the protection and development of natural values.In the course of strategic planning and the everyday operation of the town, ecological aspects have to be highlighted, and this process needs the development of the appropriate system of institutions and relationships. Now we can only see certain elements of environmental protection in the strategic settlement planning of Balmazújváros, and we seek to further enhance this process in the future.